Optimizing flu vaccine planning at NorthShore University HealthSystem - Deo, Sarang; Kolesov, Ilya; Waikar, Sachin ([London] : SAGE, 2016)
Stan Kent, VP of pharmacy at NorthShore University HealthSystem, is faced with the challenge of seasonal planning for the influenza vaccine. The supply received by the multilocation healthcare system is unreliable in terms of timing and quantity. As part of improved planning, Kent is contemplating a new contract with NorthShore's major supplier of flu vaccines. The options under consideration include fixing either the date of delivery or the quantity delivered. This case illustrates the operational complexities of the U.S. flu vaccine supply chain delivery.
Originally Published in: Deo, S., Kolesov, I., & Waiker, S. (2012). Optimizing Flu Vaccine Planning at NorthShore University HealthSystem. 5-410-750. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; North Shore University Hospital; Business logistics -- Case studies; Hospitals -- Administration -- Case studies